Hedge em carteiras de opções exóticas no Brasil - Nascimento, William Lopes (2015)
The goal of this work is to assess the empirical performance of some hedging strategies in the Brazilian derivative market. In particular, we entertain a portfolio of exotic options with knock-in and knock-out barriers. Apart from the traditional static and dynamic hedging, we also employ a hybrid strategy that combines both static and dynamic features. The empirical results show that all strategies perform statistically well, though the hybrid hedging is more efficient for it combines the accuracy of the dynamic hedging with the reduced transaction costs of the static hedging.